Overview of the Covid-19 Pandemic on Community Income in Tomuan Village, Dolock, Simalungun Regency - Eka Saudur Renaldi Sihombing (Institute of Computer Science (IOCS), 2022)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a virus that attacks the respiratory system. Disease due to viral infection is called covid-19. The purpose of this study was to see a picture of the covid-19 pandemic on people’s income in Tomuan Dolok. The design used in this study was carried out with a descriptive cross-sectional approach, where this research was conducted only in one particular period and the sampling was carried out at once, there was no repetition in data collection. From the results of the preliminary survey on the population in Tomuan Dolok by giving a questionnaire about income before and after the Covid-19 pandemic, it was found that before the occurence of Covid-19 the income of the population was still stable, whereas after the Covid-19 the income of the population descreased. The results of research conducted in Tomuan Dolok Village Simalungun Regency, obtained the results, namely : from the income group of the respondent, the respondet with lower income were 20 people (79,1%) more than the middle income and upper income groups. Of the respondents thought that the Covid-19 pandemic was more likely to think less, namely 18 people (79,1%) rather than having sufficient opinion and having a good opinion. From the results of cross tabulation between the respondent’s income group and the Covid-19 pandemic opinion, the lower income group respondents are more than (79,1%) with a score less than < 60. From the results of the research above, it is hoped that the public will maintan their health and obey the rules during the Covid-19 pandemic.